Critical thinking skills assessment instrument in physics subjects: how to develop a four tier diagnostic test?. Issue 2 (June 2021) - Waluyo, A A; Hartono,; Sulhadi,
Abstract: Critical thinking is a thinking skills that involves a process of reasoning and reflective thinking that cannot be directly observed, so it requires a separate assessment instrument. This research is a development research that aims to produce an instrument for assessing critical thinking skills that can measure students' critical thinking skills and ilustrate the interconnectedness between aspects of critical thinking skills. The sample was selected using random sampling technique of 109 students in the trial stages and 136 students in the implementation stages. Data analysis was performed through several test that is content validity, construct validity, reliability, the level of students' critical thinking skills, and analysis of variance. The validity test shows that the instrument contains 4 factors that match theorized and the content validity score shows that can be used. While the reliability test shows that the Cronbach Alpha coefficient of 0, 820. The tier of critical thinking skills of high school students in Banyumas Regency is less. Analysis of the relationship aspects of critical thinking skills shows that each aspect of critical thinking skills are interconnected with the analysis aspect as the basic and the conclusion and evaluation aspects as the culmination of being mutually sustainable in producing solutions.